Targeting Lactate Metabolism by Inhibiting MCT1 or MCT4 Impairs Leukemic Cell Proliferation, Induces Two Different Related Death-Pathways and Increases Chemotherapeutic Sensitivity of Acute Myeloid Leukemia Cells - Saulle, Ernestina; Spinello, Isabella; Quaranta, Maria Teresa; Pasquini, Luca; Pelosi, Elvira; Iorio, Egidio; Castelli, Germana; Chirico, Mattea; Pisanu, Maria Elena; Ottone, Tiziana; Voso, Maria Teresa; Testa, Ugo; et al. (Frontiers in Oncology, 2021)
Metabolism in acute myeloid leukemia (AML) cells is dependent primarily on oxidative phosphorylation. However, in order to sustain their high proliferation rate and metabolic demand, leukemic blasts use a number of metabolic strategies, including glycolytic metabolism. Understanding whether monocarboxylate transporters MCT1 and MCT4, which remove the excess of lactate produced by cancer cells, represent new hematological targets, and whether their respective inhibitors, AR-C155858 and syrosingopine, can be useful in leukemia therapy, may reveal an novel treatment strategy for patients with AML. We analyzed MCT1 and MCT4 expression and function in hematopoietic progenitor cells from healthy cord blood in several leukemic cell lines and in primary leukemic blasts from patients with AML, and investigated the effects of AR-C155858 and syrosingopine, used alone or in combination with arabinosylcytosine, on leukemic cell proliferation. We found an inverse correlation between MCT1 and MCT4 expression levels in leukemic cells, and showed that MCT4 overexpression is associated with poor prognosis in AML patients. We also found that AR-C155858 and syrosingopine inhibit leukemic cell proliferation by activating two different cell-death related pathways, i.e. necrosis for AR-C155858 treatment and autophagy for syrosingopine, and showed that AR-C155858 and syrosingopine exert an anti-proliferative effect, additive to chemotherapy, by enhancing leukemic cells sensitivity to chemotherapeutic agents. Altogether, our study shows that inhibition of MCT1 or MCT4 impairs leukemic cell proliferation, suggesting that targeting lactate metabolism may be a new therapeutic strategy for AML, and points to MCT4 as a potential therapeutic target in AML patients and to syrosingopine as a new anti-proliferative drug and inducer of autophagy to be used in combination with conventional chemotherapeutic agents in AML treatment.